Percepatan Pembangunan Desa Melalui Transformasi Digital Menuju Desa Cerdas - Nastia, Nastia; Sartika, Ika; Hugua, Hugua; Pusung, Crist Reinhard (Universitas Muhammadiyah Mataram, 2024)
This study tries to define smart villages in Indonesia. Smart villages are very similar to the concept of poverty. The increasing adoption of new technologies, especially the internet, is considered an important component of approaches to improving rural literacy. The analysis includes things like preventing villages from being protected, encouraging the use of digital technology to manage rural infrastructure, enabling workers to work remotely, and using information and communication technology in village participation and governance. To support sustainable development goals (SDGs), the United Nations formed villages into Smart Villages. SDGs consist of six main pillars: society, economy, governance, environment, life and mobility. Smart Village focuses on digital technology. This research aims to show whether villages have transformed towards digital through a literature review and bibliometric analysis, the results of which show that digital transformation in villages still receives insufficient attention.